An updated review of ethnobotany, ethnopharmacology, phytochemistry and pharmacological activities of orthosiphon stamineus Benth - Anandarajagopal Kalusalingam,; Dania Najiha Hasnu,; Abdullah Khan,; Ching, Siang Tan; Bama Menon,; Narayanan, Venkateshan; Khang, Wen Goh; Asmuni Mohd Ikmal,; Noraini Talip,; Poonguzhali Subramanian,; Long, Chiau Ming (Penerbit Universiti Kebangsaan Malaysia, 2024)
There are a myriad of potential medicinal plants worldwide. Researchers have found some, while others are still unexplored. Orthosiphon stamineus Benth. (family: Lamiaceae), commonly known as the cat's whiskers plant, is a well-known herbal plant with many medicinal uses. All the parts of O. stamineus, such as the leaves, stems, flowers, and seeds, have their uses. More than 140 pure compounds were identified and isolated from different extracts of O. stamineus, particularly leaf extracts and stem oils. Flavonoids are the most abundant phytoconstituents found in O. stamineus leaf extract. Several pharmacological activities have been studied and validated using extracts as well as pure compounds. Multiple phytoconstituents attributed to these pharmacological activities such as diuretics, antihyperglycemic, antioxidant, hepatoprotective, antiepileptic, etc., have been discovered. Considering the purported benefits of O. stamineus, the present review critically evaluates and discusses the pharmacognosy, taxonomy, ethnobotany, pharmacological activities, and phytochemistry of O. stamineus and provides updated information.